Biocontrol agents in aquaculture: Production and their application - Yuhana, Munti (Indonesian Society of Scientific Aquaculture (ISSA), 2010)
The use of biocontrol agents have become commonly accepted as a 'natural weapon' in aquaculture, either as an ecological bioremediator for low environmental quality, as well as the health promoter for cultured organisms. Biocontrol agents, which consist of beneficial microorganisms, are commonly applied as biosupplements in feeds. They are potential in replacing the use of antibiotic in inhibiting the pathogenic organisms. Therefore, their application has revealed the potential as an effective strategy to reduce the over use of antibiotics in controlling the pathogenic agents, avoid the spreading the drug resistance, or environmental deterioration of the negative effect by killing useful microorganisms. The development of suitable technology for microbial agents production, viability and stability, is a key area of research for industrial production. Production of biocontrol agents should be based on the microbial criteria, and the ability to withstand stress during processing and storage of products is crucial. This review makes an overview of biocontrol agents selection studies including techniques for isolation/identification, selection, production and its application in order to be accepted as a valuable product in aquaculture. Key words: Biocontrol agents, beneficial microorganisms, aquaculture. ABSTRAK Pemanfaatan agen biokontrol telah dapat diterima secara luas di dunia akuakultur sebagai senjata alami, baik sebagai bioremediator ekologis untuk memperbaiki kualitas lingkungan yang rendah maupun sebagai promoter/pendukung kesehatan untuk organisme-organisme yang dibudidayakan. Agen-agen biokontrol yang terdiri atas berbagai mikroorganisme yang menguntungkan umumnya diaplikasikan sebagai biosuplemen dalam pakan. Mikroorganisme tersebut potensial dalam menggantikan penggunaan antibiotik dalam proses penghambatan terhadap organisme patogenik. Oleh karena itu, aplikasinya yang sangat potensial dapat berguna sebagai strategi efektif untuk mereduksi penggunaan berlebih dari antibiotik dalam pengendalian agen patogenik, mencegah penyebaran sifat resistensi terhadap obat-obatan, atau mencegah kerusakan lingkungan dari kematian mikroorganisme yang bermanfaat. Pengembangan teknologi yang sesuai untuk produksi, viabilitas dan stabilitas dari agen biokontrol tersebut, merupakan kunci dari penelitian untuk produksi masal pada skala industri. Proses produksi dari agen biokontrol harus berdasar pada kriteria mikrobiologis. Sifat-sifat ketahanannya terhadap stress selama pemrosesan maupun penyimpanan produk adalah penting. Pada makalah ini disajikan teknik-teknik untuk isolasi, identifikasi, produksi dan aplikasi agen biokontrol untuk dapat diterima sebagai produk yang bernilai ekonomis dalam akuakultur. Kata kunci: Agen biokontrol, mikroorganisme yang menguntungkan, akuakultur.